(untitled) (Sebha University Conference Proceedings, 2024)
Cement is a fundamental material in concrete composition, making concrete structures the most common in construction compared to metal, wood, and other structures. However, cement production is also a major contributor to increased carbon dioxide emissions and global warming due to the high-temperature kilns used in its manufacturing. Laboratory studies and experiments have shown that fine glass powder can enhance the mechanical and thermal properties of concrete to some extent. In this study, we will examine ordinary concrete mixed with fine glass powder, and to achieve homogeneity, the Voigt model’s homogenization method will be used to extract the mechanical and thermal properties of this eco-friendly concrete. Additionally, Bernoulli’s mathematical model will be applied to calculate the deflection of an eco-friendly concrete beam. The results indicated a significant improvement in mechanical properties such as the modulus of elasticity and thermal expansion coefficient. Up to 35% of fine glass powder can be used as a substitute for cement, with reasonable improvements in these properties. Deflection is a critical mechanical and thermal phenomenon in the study of concrete structures, particularly in beams used in buildings, bridges, and individual houses. The results also showed that using Bernoulli’s model to calculate beam deflection reveals that increasing the proportion of fine glass powder reduces deflection. This leads to economic benefits and significant environmental advantages, including the durability of concrete and the preservation of the ecosystem through the recycling of glass waste, which contains silica, an essential component in cement composition.